1 - Positioning Universities as Engines of Innovation for Sustainable Development and Transformation - Zeleza, Paul Tiyambe (Journal of Higher Education in Africa, 2022)
This article seeks to place discourses about higher education and development in a comparative global context. It begins with brief reflections on development, by revisiting age-old debates about why some nations develop faster than others. This is an important backdrop to any meaningful discussion about the role of universities as engines of innovation for sustainable development and transformation. The article will focus mainly on the value proposition of university education and the ways in which this is reflected in its products, principally the quality of research and graduates. It will argue that, for universities to realize and sustain their institutional value, they need enabling resources, capacities and support from all key internal and external stakeholders.